Scrutinizing Defects and Defect Density of Selenium‐Doped Graphene for High‐Efficiency Triiodide Reduction in Dye‐Sensitized Solar Cells. (15th March 2018) - Meng, Xiangtong; Yu, Chang; Song, Xuedan; Iocozzia, James; Hong, Jiafu; Rager, Matthew; Jin, Huile; Wang, Shun; Huang, Longlong; Qiu, Jieshan; Lin, Zhiqun
Abstract: Understanding the impact of the defects/defect density of electrocatalysts on the activity in the triiodide (I3 − ) reduction reaction of dye‐sensitized solar cells (DSSCs) is indispensable for the design and construction of high‐efficiency counter electrodes (CEs). Active‐site‐enriched selenium‐doped graphene (SeG) was crafted by ball‐milling followed by high‐temperature annealing to yield abundant edge sites and fully activated basal planes. The density of defects within SeG can be tuned by adjusting the annealing temperature. The sample synthesized at an annealing temperature of 900 °C exhibited a superior response to the I3 − reduction with a high conversion efficiency of 8.42 %, outperforming the Pt reference (7.88 %). Improved stability is also observed. DFT calculations showed the high catalytic activity of SeG over pure graphene is a result of the reduced ionization energy owing to incorporation of Se species, facilitating electron transfer at the electrode–electrolyte interface. Abstract : Ab in die Sonne ! Selen‐dotiertes Graphen (SeG) mit angereicherten aktiven Zentren wurde durch Kugelmahlen und nachfolgendes Erhitzen auf hohe Temperaturen erhalten. Bei 900 °C gebildetes SeG (SeG‐900) lieferte als Elektrokatalysator für DSSCs eine hohe Effizienz von 8.42 %, mehr als die Pt‐Referenz (7.88 %). Dies lässt sich auf die verringerte Ionisierungsenergie infolge des Einbaus von Se‐Spezies und eine verbesserte Fähigkeit zum Ladungstransfer zurückführen.